An Account on Myxomycetes from Kathmandu Valley, Nepal - Chauhan, Ananta Bahadur; Budhathoki, Usha; Adhikari, Mahesh Kumar (Journal of Natural History Museum, 2015)
This paper reports on 11 species of myxomycetes (Arcyria pomiformis, Arcyria incarnata, Arcyria cineria, Stemoitis sp., Didymium flexuosum,Physarum viride. Hemitrichia serpula, Tubifera microsperma, Fuligo cinerea, Mucilago crustacea and Didymium iridis) gathered in 2006-2008 from the adjoining hills (Shivapuri and Godavari) around the Kathmandu valley. Further studies on the phytogeographic relationship, frequency and dominance of the taxa need to be carried out in future. J. Nat. Hist. Mus. Vol. 26, 2012: 194-197